Fatigue Properties of ADI in Dependence on Isothermal Transformation DWELL - Stanislav Vechet; Jan Kohout; Klara Hanzlikova (Communications - Scientific letters of the University of Zilina, 2004)
As a result of excellent both mechanical and technological properties, austempered ductile iron (ADI) is ranked with very perspective structural materials. Recently it has been applied even to castings for dynamically loaded components and a considerable part of ADI production is applied also in military industry. The structure of ADI matrix, mostly created by the mixture of bainite and stabilized austenite, strongly depends on transformation conditions, i.e. temperature and the length of isothermal transformation dwell. An ADI transformed at 380 °C during a temporal range from 2 minutes to 9 hours was studied in details, with emphasis on structural composition and fatigue properties. The highest level of fatigue properties was obtained for the transformation dwell of 60 minutes when the maximum portion of austenite was found in ADI structure.